MINERAL EXPLORATION IN INDIGENOUS LANDS: THE DISCURSIVE NORMALIZATION OF ILLEGAL MINING IN BRAZIL - Volcan, Taiane de Oliveira (AoIR Selected Papers of Internet Research, 2023)
In 2023, the world faced a humanitarian tragedy in Brazil involving the Yanomami people. In addition to the result of criminal conduct of public policies aimed at indigenous peoples in the last four years, the case highlights a culture of erasure of Brazilian native peoples that permeates society, institutions, and the mainstream press. In this work, we discuss how mining in indigenous lands has been approached discursively in Brazil. For this, we analyze the conversations on Twitter related to #AtoPelaTerra, a protest in defense of the environment and against the bill that authorizes mining in indigenous lands, held in Brasília in March 2022. To understand the conversation dynamics of the publications collected, we performed a network analysis (WASSERMAN & FAUST, 1994) and to analyze the speeches produced by the subjects who participated in the debate, we adopted the Analysis of Connected Concepts (LINDGREEN 2016). Our results demonstrate that the conversation about the indigenous agenda has been polarized and with a strong misinformation content, especially in the field of the extreme right. In addition, the defense of native peoples and environmental preservation has a limited scope to its most active militancy. In the mainstream media, both the environmental agenda and the indigenous agenda are softened by replacing the term “mining” with “mineral exploration”, which ends up normalizing (FOUCAULT, 2003) practices that are harmful to the environment and indigenous peoples, as an effect of a crossing of the economic and supposedly developmentalist debate that prevails in these spaces.